PROFITABILITY MODERATES THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) AND INDEPENDENT BOARDS OF COMMISSIONERS ON COMPANY VALUE - Rudi Harianto (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This research aims to analyze the effect of Corporate Social Responsibility (CSR) and independent board of commissioners on company value with profitability as a moderation in Manufacturing Companies on the Indonesia Stock Exchange in 2021-2023. This study uses a quantitative approach. The sampling technique used in this study using a purposive sampling approach after the sampling technique was carried out, the companies used in the study were 29 companies with a total observation year of 3 years so that the sample data used was 87 data on manufacturing companies on the Indonesia Stock Exchange in 2021-2023, The data analysis technique used moderation regression analysis. The results of this study indicate that Corporate Social Responsibility (CSR) has an effect on company value, an independent board of commissioners has an effect on company value, profitability has an effect on company value, profitability can be a moderation between Corporate Social Responsibility (CSR) and company value, and profitability can be a moderation between an independent board of commissioners and company value.